Efektivitas Pembiayaan Hijau dalam Perspektif Hukum Pembangunan Berkelanjutan: Studi Kasus Penambangan Nikel di Morowali - Prabowo, Boma Indra (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Green financing is a strategic approach to promoting sustainable development, especially in extractive sectors such as nickel mining. This article analyzes the effectiveness of green financing implementation by Indonesian banks in preventing environmental damage caused by mining activities in Morowali. This study uses a socio-legal approach with a normative-empirical method. Data collection was conducted through three main methods: semi-structured interviews, document analysis, and limited field observations. The findings indicate that despite formal regulations such as POJK 51/2017 and the OJK Roadmap, implementation on the ground remains weak due to insufficient oversight, the absence of sanctions, and the dominance of an economic profit-driven paradigm. Green financing has not functioned as a tool for ecological justice because it does not address the structural root causes within the financial system. This study recommends enhancing oversight and enforcement of sanctions, as well as the need to integrate sustainability values into the financing process. The novelty of this study lies in the integration of a sustainable development legal approach to assess the effectiveness of green financing policies in the real-world case of Indonesia's mining sector.